EVALUASI PENERAPAN PERSONAL HYGIENE PADA COOK DI KITCHEN LABERSA GRAND HOTEL AND CONVENTION CENTER PEKANBARU - Erly, Zania Buchi; Sidiq, Siti Sofro (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
In the service needs needed in tourism business not only displays quality, cuisine and comfort, however, the important factor is comfort and guarantees that are suitable for the purpose of people enjoying tha facility. Personal hygine is an individual effort to take care of one’s own health, apprearance and environment This research purpose to determine the application of personal hygiene in the cook kitchen at labersa grand hotel and convention center which is located on Jalan labersa, parit indah, pekanbaru.This research uses a qualitative methods with a descriptive approach in which the data obtained are analyzed based on the ability of the investigator's reasoning in connecting information, facts and data by presenting observations, interviews and analyzing problems found in the field, so that a clear picture of the object under research can be obtained and can be draw clear conclusions. The results of this indicate the application of personal hygiene in cook at the kitchen labersa grand hotel and convention center is an not accordance with existing operational standard procedures Keywords : Personal Hygiene, Cook, Kitchen, Hotel